PENGARUH WORD OF MOUTH (WOM), HARGA "TIKET EARLY BIRD", DAN CELEBRITY ENDORSEMENT TERHADAP PEMBELIAN. (STUDI KASUS PADA PEMBELIAN TIKET KONSER FESTGO DI UNIVERSITAS MUHAMMADIYAH GOMBONG) - Fatkhurrokhman, Tiyan; Anggoro, Wisanggeni Bagus; Pratama, Wilson Chandra Teguh (MANAJEMEN DEWANTARA, 2024)
This study aims to analyze the influence of Word of Mouth (WOM), "Early Bird" ticket pricing, and Celebrity Endorsement on ticket purchase decisions for the Festgo concert event at Universitas Muhammadiyah Gombong. A quantitative approach using a survey method was employed, involving 100 randomly selected respondents. Data were collected through questionnaires and analyzed using SPSS software. The findings indicate that all three variables have a positive and significant impact on ticket purchase decisions. WOM plays a crucial role in shaping consumer perceptions, while "Early Bird" pricing and Celebrity Endorsement enhance purchase interest. This research contributes to marketing strategies in the concert industry and suggests that event organizers integrate these three factors to improve ticket sales effectiveness. Limitations of this study include its specific context and limited sample size, prompting recommendations for future research to explore a broader range of variables and contexts.